PERSEPSI MAHASISWA TERHADAP PRODUK KOSMETIK YANG TIDAK BERLABEL HALAL DITINJAU DARI PERILAKU KONSUMEN (Studi Kasus Mahasiswi Hukum Ekonomi Syariah Angkatan 2018 INSURI Ponorogo) - Umi Mubarokah; Suad Fikriawan; Diyan Putri Ayu (Social Science Academic, 2023)
In the current era of globalization, the role of government supervision in regulating the distribution of cosmetics must always be done by improving the quality of consumer protection. For this reason, the Indonesian Ulema Council (LPPOM MUI) has a strong task of researching, reviewing, analyzing and deciding whether food products and their derivatives, medicines and cosmetic products are safe for consumption. in terms of health and in terms of teaching Islam. For this reason, consumers must know what are the factors that influence consumer behavior towards cosmetic products that are not labeled halal? And what is the perception of the 2018 Islamic economic law students regarding cosmetic products that are not labeled halal?. The purpose of this study was to find out the perceptions of Islamic economic law students class 2018 about cosmetics that are not labeled halal in relation to consumer behavior. The nature of this research is field research. The type of research used in this research is descriptive and uses data collection techniques using interviews, documentation, and observation. In an interview with a 2018 Islamic Economic Law student, the data was processed using a qualitative analysis method using the inductive reasoning method. Based on the results of the study, the most dominant factor influencing consumer behavior in purchasing non-halal labeled cosmetic products by students of the Faculty of Sharia class 2018 INSURI Ponorogo includes several factors, namely close friends, self factors and environmental factors.